ENERGY AWARE ZONE ROUTING PROTOCOL FOR MANET - GSR, EMIL SELVAN; N, GAYATHRI; RAI, ANKUSH; R, JAGADEESH KANNAN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Mobile Ad hoc Network (MANET) is a dynamic network consisting of a collection of wireless mobile nodes that communicate with each other without the need of centralized authority. Each node can send and receive data, and it should also forward routing information unrelated to its own use. Routing protocols in MANET establish path between source and destination based on number of hops. Establishment of shortest path alone is not sufficient to prolong the network lifetime. Energy consumption reduction methods are necessary as the nodes in MANET are restricted by battery supply. Energy is drained when the MANET nodes transmit and receive the data. For itself, energy management techniques are necessary in order to improve the performance of the routing protocol. Both proactive and reactive protocols have trade-off in them. ZRP is a hybrid protocol which overcomes the shortcomings of proactive and reactive routing protocols. ZRP divides the entire network into zones of variable size where routing inside the zone is performed using proactive routing approach and exterior to zone is performed using reactive routing approach. The performance characteristics of the ZRP protocol are established through simulations by comparing it to well-known routing protocol namely AODV.